Modeling robocasting with smoothed particle hydrodynamics: Printing gap-spanning filaments - Dietemann, Bastien; Bosna, Fatih; Lorenz, Mylena Mayara; Travitzky, Nahum; Kruggel-Emden, Harald; Kraft, Torsten; Bierwisch, Claas (Additive Manufacturing, 2020)
The meshfree method Smoothed Particle Hydrodynamics (SPH) is used to model Robocasting (RC), a Material Extrusion based Additive Manufacturing (EAM) processes, in which ceramic filaments are extruded through a robotically controlled nozzle. One characteristic feature of RC is its capability to form gap-spanning filaments. In this paper, we focus on a numerical study of this feature as a function of material properties. The result is a process map, which allows for the identification of rheology parameters yielding (i) suitable process results, (ii) a too liquid ceramic paste which cannot form gap-spanning filaments or (iii) a paste which is not processable due to too large stiffness. With the help of this map, process guidelines are derived on how material properties in terms of paste rheology have to be tailored to obtain a certain filament deflection or, in contrast, straight filaments without any deflection into the gap. Our study is one particular example for RC but the numerical approach is transferable to other EAM techniques as well. Advantages and limitations of SPH for modeling of EAM are discussed. Guidelines are derived towards further improvements of future studies of EAM with SPH.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Material extrusion; Numerical modeling; Process design